Understanding outcome metrics of the revised NIOSH lifting equation. (November 2019) - Fox, Robert R.; Lu, Ming-Lun; Occhipinti, Enrico; Jaeger, Matthias
Abstract: The interpretation of the calculated result of the revised NIOSH Lifting Equation (RNLE) has been problematic because the relationship of the calculated result to back injury risk has not always been either well understood nor consistently interpreted. During the revision of the ISO standard 11228–1 (Manual lifting, lowering and carrying), an extensive literature review was conducted on validation studies of the RNLE. A systematic review of exposure-risk associations between the LI metrics and various low-back health outcomes from peer-reviewed epidemiological studies was conducted. Risk interpretations for different levels of calculated result of the RNLE are added to the ISO standard. Rationale for the risk interpretations is presented in this paper. Highlights: The NIOSH Lift Index alone reflects "exposure" and risk can be mapped to it. Use a 1.5 Lift Index as the threshold between low and moderate risk for back pain. Consider other lifting assessment methods to supplement the NIOSH equation. Consider NIOSH lift equation extensions to address specific lifting situations.